Perlindungan Nasabah Terhadap Klausula Eksonerasi Dalam Akad Pembiayaan Murabahah Dalam Perspektif Hukum Islam Dan Hukum Positif - Maulana, Anaia Gaizka; Priyatama, Alwan Brilliant; Nugroho, Krisna Akbar; Triyanta, Agus; Baity, Sheila Noor (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
An exoneration clause in a murabaha financing agreement that exempts Islamic financing institutions from responsibility for losses arising from a transaction. To ensure clarity and legal protection, the agreement in murabaha financing transactions is used as a formal tool. However, some business actors have misused this agreement by including a risk transfer clause to the customer to obtain greater profits. This paper aims to review and analyze the validity and legal protection of the inclusion of such clauses in murabaha financing agreements. The research is conducted normatively with the approach of legislation, positive law theory, Al-Quran, Hadith and Fiqh. The results of the analysis show that according to positive law, including Islamic Law and Law No. 8 of 1999 concerning Consumer Protection, the clause transferring the responsibility of the Business Actor to the Customer in the murabaha financing agreement is declared null and void. The responsibility for the risk is legally borne by The Business Actor. As a result, the murabahah financing agreement is considered invalid from the start and cannot be used to transfer ownership rights. The law governing this agreement is based on the principle of Lex Specialis Derogat Legi Generali, where Islamic Law has more specific power than the General Provisions of Civil Law.